Design of resolution adaptive TIQ flash ADC using AMS 0.35 µm technology. (12th June 2009) - Rajashekar, G.; Bhat, M.S.
This paper presents a resolution adaptive flash A/D converter design and its performance. To achieve high speed, the proposed A/D converter utilises threshold inverter quantisation technique replacing conventional analogue comparators with digital comparators. The replacement results in a faster digital conversion and a reduction of the analogue nodes in the ADC. The proposed ADC is a true variable resolution ADC, operates at 3-bit, 4-bit, 5-bit and 6-bit precision depending on control inputs. The proposed ADC is designed with AMS 0.35 μm CMOS technology and 3.3 V power supply voltage and a prototype chip is fabricated. Simulation results and test results are presented.